Inhabiting la patria : identity, agency, and antojo in the work of Julia Alvarez - Harrison, Rebecca L., 1970-; Hipchen, Emily, 1964- (State University of New York Press, 2013)
"Provides insightful criticism from many perspectives and grants in-depth analyses of both well-known and lesser studied texts"--Provided by publisher
Keywords: Alvarez, Julia -- Criticism and interpretation.; Alvarez, Julia; Dominican literature -- History and criticism.; Littérature dominicaine -- Histoire et critique.; LITERARY CRITICISM -- American -- General.; Criticism, interpretation, etc.